Examining post-conflict stressors in northern Sri Lanka: A qualitative study - Thomas, F.C.; Souza, M.D.; Magwood, O.; Thilakanathan, D.; Sukumar, V.; Doherty, S.; Dass, G.; Hart, T.; Sivayokan, S.; Wickramage, K.; Kirupakaran, S.; McShane, K. (PLOS ONE, 2022)
Citation: Thomas FC, D’souza M, Magwood O, Thilakanathan D, Sukumar V, Doherty S, et al. (2022) Examining post-conflict stressors in northern Sri Lanka: A qualitative study. PLoS ONE 17(9): e0267018.